Christology and the synoptic problem an arguement for Markan priority - Head, Peter M. (Cambridge, UK Cambridge UP, 1997)
Includes bibliographical references and index.
Keywords: Bible. N.T. Mark -- criticism, interpretation, etc; Bible. N.T. Matthew -- criticism, interpretation, etc; Griesbach hypotheses (Synoptic criticism).; Jesus Christ -- history of doctrines -- early church, ca 30-600.